Phenotypic variation in three populations of Campanula rotundifolia L. in northern lower Michigan. - Lehnen Jr. , Larry P. (1982)
http://deepblue.lib.umich.edu/bitstream/2027.42/53534/1/1969.pdf Description of 1969.pdf : Access restricted to on-site users at the U-M Biological Station.